Russian intelligence files on Asia. (Leiden, The Netherlands)
1 mikrofilm makarası (581 poz)
Keywords: General intelligence on the Turkish army, and on the domestic and foreign policy of the country. Geographical, topographical, statistical, ethnographical and hydrographical intelligence : Geographical and topographical intelligence : European and Asian Turkey.